2012
DOI: 10.4038/jnsfsr.v40i4.5044
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of fluoride in groundwater of Sri Lanka

Abstract: Fluoride ions in drinking water is well known for both beneficial and detrimental effects on health. Millions of inhabitants in the Dry Zone of Sri Lanka are vulnerable to fluorosis due to consumption of high fluoride groundwater. The objective of this study is to upgrade the spatial distribution map of groundwater fluoride levels in Sri Lanka. The map was prepared using nearly 14000 groundwater fluoride data that were collected from primary and secondary sources. The fluoride map of Sri Lanka indicates that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 8 publications
1
44
1
1
Order By: Relevance
“…Recent investigations have shown that even within a few years, groundwater wells in the dry zone of Sri Lanka have shown a marked increase of fluoride changing from safe levels to -not recommended‖ levels (Chandrajith et al, 2012). The climate change and the consequent evapotranspiration have been very high in these tropical lands with the resulting elevations of fluoride, Na, Ca and Mg in the groundwater.…”
Section: Geochemistry Of Groundwater Fluoridementioning
confidence: 99%
See 2 more Smart Citations
“…Recent investigations have shown that even within a few years, groundwater wells in the dry zone of Sri Lanka have shown a marked increase of fluoride changing from safe levels to -not recommended‖ levels (Chandrajith et al, 2012). The climate change and the consequent evapotranspiration have been very high in these tropical lands with the resulting elevations of fluoride, Na, Ca and Mg in the groundwater.…”
Section: Geochemistry Of Groundwater Fluoridementioning
confidence: 99%
“…A clear discrimination between the fluoride and Ca/Mg ratios can be observed for the CKDu and nonCKDu drinking water wells (figure 4). Although higher hardness (Ca + Mg) and fluoride is a common factor in most of the dry zone of Sri Lanka (Chandrajith et al, 2012), the Mg-factor is extremely important in the case of CKDu foci in the dry zone of Sri Lanka. While calcium has been given very high prominence, magnesium has been grossly underestimated even though it plays a major role in cardioprotectivity and its calcium antagonistic properties.…”
Section: Magnesium Deficiency As a Risk Factor For Ckdumentioning
confidence: 99%
See 1 more Smart Citation
“…The community fluorosis index (CFI), based on a 2002 survey among schoolchildren in three schools in high fluoride groundwater areas (>1.5 mg/l up to 10.9 mg/l) of Anuradhapura District, found CFI values in the range 1.85 -2.29 [3] A landmark publication on medical geology in Sri Lanka has noted that dental fluorosis frequently occurs when the fluoride content of drinking water exceeds 1.5 mg/l, and such water is habitually consumed by young children [4]. The findings of this publication have been extended by a later study, which provides a map of Sri Lanka based on fluoride levels of 14,500 samples of groundwater from both shallow and deep wells in 45 locations in seven Provinces, excluding the Central and Northern Provinces [5]. According to this study, vast swathes of the North Central, Eastern and Uva Provinces have groundwater concentrations between 1.0 and 1.5 mg/l, with many areas within them having between 1.5 and 2.0 mg/l, and other locations having over 2.0 mg/l.…”
Section: Introductionmentioning
confidence: 67%
“…Paper are of particular significance because they define, many localised variations in fluoride content of groundwater within Districts and also within many villages, that would explain the scattered distribution of clinically apparent dental fluorosis among people living in contiguous land areas [4,5,7].…”
Section: No 4 December 2017mentioning
confidence: 99%